Preparation method and application of irru / tion acidic oxygen evolution reaction electrocatalyst

CN122543093BActive Publication Date: 2026-10-09ZHEJIANG KAIDA CATALYTIC NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611038444.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-09
Estimated Expiration
2046-07-13

AI Technical Summary

Technical Problem

[0005]但申请人发现,上述技术方案制备的IrRu/TiOxNy纳米带复合催化剂的缺点是催化活性仍然偏低(在10mA/cm2的电流密度下,过电位为250mV),且同时稳定性也不够理想,仍存在不小的改进空间

Benefits of technology

(1)本发明通过优化制备顺序和氮化温度,更有利于形成具有更强电子供给能力的TiON多孔纳米带,更好地诱导电子从TiON和Ir位点向Ru位点转移,形成“电子供给库效应”,一方面为Ru位点更好地提供充足的电子补偿,持续稳定其低价态,另一方面可促进形成更高活性的高价态Ir物种,从而有效改善催化活性和稳定性,在质子交换膜水电解槽装置中表现出极大的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122543093B_ABST
    Figure CN122543093B_ABST
Patent Text Reader

Abstract

The application relates to the field of electrolysis of water, and discloses a preparation method and application of an IrRu / TiON acidic oxygen evolution reaction electrocatalyst. The preparation method of the IrRu / TiON acidic oxygen evolution reaction electrocatalyst comprises the following steps: 1) TiON porous nanobelt preparation: sodium titanate nanobelts are prepared through a hydrothermal reaction of TiO2, NaOH and a surfactant; the sodium titanate nanobelts are dispersed in an acid solution to obtain hydrogen titanate nanobelts through an ion exchange reaction; the hydrogen titanate nanobelts are nitrided in a nitrogen atmosphere to obtain TiON porous nanobelts; and 2) preparation of the IrRu / TiON acidic oxygen evolution reaction electrocatalyst: Ir precursors and Ru precursors are dispersed in a polyol, TiON porous nanobelts are added, and a reduction reaction is conducted to obtain the IrRu / TiON acidic oxygen evolution reaction electrocatalyst. The IrRu / TiON acidic oxygen evolution reaction electrocatalyst prepared through the optimized preparation method has better catalytic activity and stability, and can be applied to proton exchange membrane water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water electrolysis, and more particularly to a method for preparing and applying an IrRu / TiON acidic oxygen evolution reaction electrocatalyst. Background Technology

[0002] Compared to alkaline water electrolysis, proton exchange membrane electrolysis (PEMWE) offers higher energy conversion efficiency and hydrogen purity, faster response time, and lower ohmic losses, making it better suited for coupling with renewable energy sources such as wind, hydro, and solar power. It is considered a crucial technology for producing high-purity green hydrogen. However, the slow kinetics of the anodic oxygen evolution reaction (OER), involving four-proton coupled electron transfer, are a key factor limiting the overall efficiency of PEMWE. Furthermore, the strong acidity and oxidation environment of the anode pose significant challenges to the activity and stability of the electrocatalyst. Ru-based catalysts, due to their good intrinsic activity and relatively low cost, have become a research hotspot in this field. However, excessive oxidation at high anode potentials generates soluble high-valence Ru species, leading to a rapid decline in their catalytic activity and stability. Therefore, finding a better balance between the activity, stability, and cost-effectiveness of Ru-based electrocatalysts is a critical issue that needs to be addressed for the commercial application of PEMWE.

[0003] Maintaining the low valence state of Ru sites by introducing electron donors near the Ru sites is the ideal strategy for achieving a balance between Ru-based catalytic activity and stability. Firstly, Ir doping has been proven to be an effective method for replenishing electrons to Ru sites. However, relying solely on Ir sites to provide electrons is insufficient to maintain the low valence state of Ru sites under complex acidic OER conditions for extended periods. Furthermore, excessive Ir doping undoubtedly increases costs and may sacrifice intrinsic activity due to instability. Secondly, carbon materials, nitrides, and carbide supports with high electron-donating capabilities are easily oxidized during OER processes, leading to structural instability and hindering their ability to effectively provide electrons to Ru sites. Conversely, metal oxide supports with high thermodynamic stability (such as TiO2) have limited electron-donating capabilities to Ru sites. Thirdly, suitable low-dimensional structures can form directional electron transport channels, accelerating electron replenishment from the support to the active site. Therefore, designing a suitable low-dimensional electron donor support that continuously provides electrons to Ru sites and promotes electron transfer from Ir sites to Ru sites is crucial for achieving a balance between activity and stability in acidic OER electrocatalysts.

[0004] Patent application number 202411535010.5 discloses an IrRu / TiO3 mixture. x N yNanoribbon composite catalyst and its preparation method. First, IrRu alloy was loaded onto a titanium-containing nanoribbon support using ethylene glycol reduction. Then, the support was placed in the center of a tube furnace, evacuated, and NH3 was introduced. The furnace was heated to 500–600 °C under flowing NH3 and held for 1–5 h. After cooling to room temperature, IrRu / TiO2 was obtained. x N y Nanoribbon composite catalyst.

[0005] However, the applicant discovered that the IrRu / TiO prepared by the above technical solution x N y The drawback of nanoribbon composite catalysts is that their catalytic activity remains relatively low (around 10 mA / cm²). 2 At a current density of 250mV, the overpotential is 250mV, and the stability is not ideal, so there is still considerable room for improvement. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a method for preparing and applying an IrRu / TiON acidic oxygen evolution reaction electrocatalyst. By optimizing the preparation method, this invention first prepares porous TiON nanoribbons, and then uniformly loads IrRu nanoalloys onto the porous TiON nanoribbons at a relatively low temperature, thus obtaining an IrRu / TiON acidic oxygen evolution reaction electrocatalyst with better catalytic activity and stability, which can be applied in proton exchange membrane water electrolysis.

[0007] The specific technical solution of this invention is as follows: First, this invention provides a method for preparing an IrRu / TiON acidic oxygen evolution reaction electrocatalyst, such as... Figure 1 As shown, it includes the following steps: 1) Preparation of TiON porous nanoribbons: Sodium titanate nanoribbons were prepared by hydrothermal reaction of TiO2, NaOH and surfactant in water; the sodium titanate nanoribbons were dispersed in an acid solution for ion exchange reaction to obtain hydrogen titanate nanoribbons; the hydrogen titanate nanoribbons were placed in an NH3 atmosphere for multi-stage nitriding and cooling to obtain TiON porous nanoribbons.

[0008] 2) Preparation of IrRu / TiON acidic oxygen evolution reaction electrocatalyst: Ir precursor and Ru precursor were dispersed in polyol, and TiON porous nanobelts were added and dispersed evenly to obtain a suspension. After reduction reaction at 140~160℃, IrRu / TiON acidic oxygen evolution reaction electrocatalyst with a total loading of Ir and Ru elements of 30~50wt% was obtained.

[0009] As described in the background section, patent 202411535010.5 first uses ethylene glycol reduction to load IrRu alloy onto a titanium-containing nanoribbon support, and then nitrides it at 500~600℃ to obtain IrRu / TiO.x N y Nanoribbon composite catalyst. The drawback of this method is that the catalytic activity remains relatively low (around 10 mA / cm²). 2 At a current density of 250 mV, the overpotential is 250 mV, and the stability is also poor. Therefore, this invention optimizes the preparation method by first preparing TiON porous nanoribbons, and then uniformly loading IrRu nanoalloy onto the TiON porous nanoribbons at a lower temperature. The catalyst obtained by this method has better catalytic activity and stability.

[0010] The reason for this is that the order of preparing TiON porous nanoribbons first and then loading IrRu nanoalloys according to this invention is more conducive to forming an "electron supply pool effect" to enhance the electronic interaction between the TiON porous nanoribbon support and the IrRu nanoalloy in the electrocatalyst, thereby effectively solving the problem of poor catalytic activity and stability of electrocatalysts for the acidic oxygen evolution reaction. However, if the preparation process of the aforementioned patent is followed, it is difficult to form the "electron supply pool effect," as detailed below: The mechanism of the "electron donor pool effect" is as follows: Since the electronegativity of nitrogen (3.04) is lower than that of oxygen (3.44), when nitrogen atoms replace some oxygen atoms in the TiO2 lattice, donor levels are introduced into the band gap, causing the support to exhibit n-type semiconductor characteristics. When the IrRu alloy comes into contact with electron-rich TiON, due to the difference in their work functions, electrons spontaneously flow from TiON to the metal, forming an electron accumulation layer at the metal-support interface, i.e., the "electron donor pool." This effect further optimizes the adsorption energy of active sites for reaction intermediates (such as ·OH, ·O, ·OOH, etc.), thereby improving the catalytic activity of OER.

[0011] In this invention: TiON porous nanoribbons are first obtained by high-temperature nitriding (700~800℃), and then loaded with metal under mild conditions (140~160℃) with polyol reduction. The key to this sequence is that the hydrotitanic acid nanoribbons are independently nitrided in an NH3 atmosphere at 700~800℃, allowing O atoms in the lattice to be fully and uniformly replaced by N atoms, forming well-crystallized TiON porous nanoribbons with high N doping concentration and stable electronic structure. At this point, the electron-rich characteristics of the support are fully established. Subsequently, IrRu alloy is loaded onto the TiON surface by polyol reduction. This process is at a low temperature, which does not destroy the TiON lattice structure or cause interdiffusion of interfacial elements. When the IrRu nanoalloy comes into contact with TiON, the difference in work function between the two drives electrons to transfer from TiON to IrRu, forming a distinct electron supply layer at the interface. Since TiON already possesses a complete highly conductive n-type semiconductor structure before contact, the electron transfer channel is unobstructed, and the effect is significant.

[0012] In patent 202411535010.5: metal is first loaded (on a titanium-containing nanoribbon support), and then co-nitrided in NH3 at 500-600℃. The order is the reverse of this invention. In the NH3 atmosphere at 500-600℃, the original titanium-containing nanoribbons gradually transform into TiON, while the loaded IrRu alloy is also in a high-temperature environment. The following situations occur during this process: ① Metal participates in the nitriding reaction: Ir and Ru are prone to surface nitriding or forming a thin layer of metal nitrides at high-temperature NH3, changing their surface electronic structure; ② The nitriding process of the support is interfered with by the IrRu alloy: IrRu alloy particles will hinder the contact between NH3 and the support surface, resulting in uneven local nitriding; ③ Interfacial interdiffusion: At high temperatures, Ti, O, and N in the support and Ir and Ru in the metal may undergo atomic interdiffusion, forming a blurred mixed interface rather than a clear heterojunction. Because the TiON support in this patent is generated in situ in the presence of an IrRu alloy, its N doping degree, crystallinity, and Fermi level position differ significantly from the TiON formed by independent nitriding in this invention. More importantly, if a mixed transition layer of Ir-Ru-Ti-ON is formed at the interface, the electron-rich properties of the support cannot be directly transferred to the metal surface. Electrons may be gradually dissipated or localized in the interface transition layer, failing to form effective electron accumulation on the metal surface, i.e., failing to form an "electron pool effect".

[0013] Furthermore, the nitriding temperature is crucial for the formation of the "electron supply pool effect." In patent 202411535010.5, the nitriding temperature is only 500~600℃, while in this invention it is 700~800℃. This invention finds that within this nitriding temperature window, the formation of the "electron supply pool effect" is more favorable. The reason for this is that when the nitriding temperature is low, such as 600℃, the number of N atoms replacing O atoms in the TiO2 lattice is insufficient, making it impossible to form a TiON crystalline phase with good conductivity, which hinders the electron transport efficiency at the interface, thereby weakening the "electron supply pool effect." When the nitriding temperature is too high, such as exceeding 800℃, it will destroy the porous nanoribbon structure of TiON, affecting the uniform loading of IrRu nanoalloys, which is not conducive to the formation of the "electron supply pool effect."

[0014] It should be noted that through our experiments, we found that it is actually difficult to further increase the nitriding temperature in patent 202411535010.5. The reason is that, according to the order of loading the active metal first and then nitriding in this patent, if the nitriding temperature is too high, the active metal will agglomerate due to high-temperature sintering, which will affect the catalytic activity and stability.

[0015] In summary, the two preparation sequences and the nitriding temperature together determine whether an "electron supply pool effect" can be formed. The fundamental reason why the process of this invention can form an "electron supply pool effect" is that the carrier electronic structure engineering is placed before the metal-interface construction and the nitriding temperature is appropriately increased. This ensures that the TiON porous nanoribbons with high conductivity and high n-type carrier concentration form a clear, diffusion-free heterojunction with the IrRu alloy, allowing electrons to be effectively transferred from the carrier to the metal. In contrast, existing patents couple the metal load and carrier nitriding in the same heat treatment step, resulting in interdiffusion, competitive reactions, and structural reconstruction at the interface, which disrupts the directional electron transfer channel from the carrier to the metal. At the same time, the nitriding temperature is too low, thus failing to construct a clear "electron supply pool effect."

[0016] Furthermore, we found that a higher loading of active metal is beneficial for forming a complete metal-support interface, which in turn is more conducive to the formation of the "electron supply pool effect," enhancing the metal-support interaction and further stabilizing the metal nanoparticles. Ultimately, this invention limits the total loading of Ir and Ru elements to 30-50 wt%. Further, due to the higher loading of active metal in the catalyst of this invention, a relatively mild (140-160℃) polyol reduction method is more conducive to the formation of the "electron supply pool effect." This is because if the reduction temperature is higher, the high-loading active metal is prone to agglomeration, increasing the particle size and weakening the "electron supply pool effect." At the higher loading of this invention, using polyol reduction at 140-160℃, the average particle size of the IrRu nanoparticles is still only 2.05 nm (…). Figure 4 ), and uniformly dispersed on TiON porous nanoribbons ( Figure 4 and Figure 6 This provides favorable preconditions for the formation of the "electronic supply pool effect".

[0017] Preferably, in step 1), the multi-stage nitriding includes: first, heating to 400-450°C at a rate of 3-7°C / min and holding for 1-3 hours, then heating to 700-800°C at a rate of 3-7°C / min and holding for 2-4 hours. This invention has found that the above-mentioned multi-stage nitriding process can further facilitate the formation of an "electron bank effect." The specific principle is as follows: the nitriding process is controlled by diffusion kinetics. This invention first proceeds at a lower temperature (400-450°C), where ammonia begins to gradually decompose, producing a small amount of active nitrogen atoms, which is beneficial for forming a uniform and highly dispersed TiON layer on the TiO2 surface. Then, the temperature is increased (700-800°C) to accelerate the decomposition of ammonia, promoting the formation of a large number of active nitrogen atoms. The high temperature also accelerates the diffusion of nitrogen atoms, thereby effectively improving the nitriding efficiency and uniformity, and promoting the formation of well-crystallized, highly N-doped, and electronically stable TiON porous nanoribbons. In contrast, a single nitriding process easily results in excessively high surface nitrogen concentration, which is not conducive to further nitrogen atom diffusion and affects the nitriding efficiency.

[0018] Preferably, in step 1), the hydrothermal reaction specifically includes: adding TiO2, NaOH and surfactant into water, stirring evenly, and then hydrothermally reacting at 160~200℃ for 12~36 hours. After cooling, the solid and liquid are separated, the precipitate is taken, washed, and dried to obtain sodium titanate nanoribbons.

[0019] Preferably, in step 1), the mass ratio of TiO2, NaOH and surfactant is 1:(5~10):(0.5~1).

[0020] Preferably, the surfactant is hexadecyltrimethylammonium bromide (CTAB).

[0021] Preferably, in step 1), the washing includes: first washing the precipitate with water until neutral, and then washing with anhydrous ethanol to completely remove the surfactant.

[0022] Preferably, in step 1), the acid solution is a 0.1~0.5 mol / L HCl solution.

[0023] Preferably, in step 1), the ion exchange reaction takes 2 to 4 hours.

[0024] Preferably, in step 1): after the ion exchange reaction, the reaction product is filtered, washed with water until neutral, and dried to obtain hydrotitanic acid nanoribbons.

[0025] Preferably, in step 2), the molar ratio of Ir element in the Ir precursor to Ru element in the Ru precursor is (1:3) to (3:1).

[0026] Preferably, in step 2): the Ir precursor is IrCl3 and / or its aqueous compound; the Ru precursor is RuCl3 and / or its aqueous compound.

[0027] Preferably, in step 2), the polyol is ethylene glycol.

[0028] Preferably, in step 2): the temperature of the reduction reaction is 140~160℃ and the time is 2~4 hours; after the reduction reaction, the reaction product is cooled to room temperature, centrifuged, the precipitate is repeatedly washed with anhydrous ethanol, and dried to obtain the IrRu / TiON acidic oxygen evolution reaction electrocatalyst.

[0029] Preferably, the drying is performed under vacuum at 50~70°C.

[0030] Secondly, this invention provides the application of the above-mentioned IrRu / TiON acidic oxygen evolution reaction electrocatalyst in proton exchange membrane electrolysis of water: the IrRu / TiON acidic oxygen evolution reaction electrocatalyst is used as an anode electrocatalyst.

[0031] Compared with the prior art, the beneficial effects of the present invention are: (1) By optimizing the preparation sequence and nitriding temperature, this invention is more conducive to forming TiON porous nanoribbons with stronger electron supply capacity, and better induces electrons to transfer from TiON and Ir sites to Ru sites, forming an "electron supply pool effect". On the one hand, it provides sufficient electron compensation for Ru sites and continuously stabilizes its low valence state. On the other hand, it can promote the formation of higher valence state Ir species with higher activity, thereby effectively improving catalytic activity and stability, and showing great application prospects in proton exchange membrane water electrolyzer devices.

[0032] (2) In the IrRu / TiON acidic oxygen evolution reaction electrocatalyst prepared according to the method of the present invention, the TiON porous nanobelt has a hierarchical porous structure and significantly reduces the synthesis temperature of IrRu nanoparticles. Therefore, the electrocatalyst of the present invention has a larger specific surface area, and the IrRu nanoparticles are more uniformly distributed and smaller in size. Attached Figure Description

[0033] Figure 1 This is a schematic diagram of the preparation process of the IrRu / TiON acidic oxygen evolution reaction electrocatalyst of the present invention; Figure 2 XRD patterns of TiON-1, IrRu NP, and IrRu / TiON-1; Figure 3 SEM images of IrRu / TiON-1 (a) in Example 1 and IrRu / TiON-CS6 (b) in Comparative Example 6; Figure 4TEM (a) and HRTEM (b) images of IrRu / TiON-1 (inset shows the size distribution of the IrRu nanoalloys); Figure 5 Nitrogen adsorption-desorption isotherms (a) and Barrett-Joyner-Halenda (BJH) pore size distribution curves (b) for IrRu / TiON-1. Figure 6 AC-HAADF-STEM image (a) and corresponding elemental distribution map (b) of IrRu / TiON-1; Figure 7 AC-HAADF-STEM image of IrRu nanoparticles and their corresponding FFT pattern and crystal structure model (a), and line scan EELS spectrum of the interface between TiON-1 support and IrRu nanoparticles (b). Figure 8 AFM image (a) and surface potential map (b) of IrRu / TiON-1; the inset in (b) shows the surface potential difference between IrRu and TiON-1; Figure 9 A schematic diagram of the "electron supply pool effect" in IrRu / TiON-1; Figure 10 For IrRu / TiON-1, IrRu NP, commercial IrO2, commercial RuO2, IrRu / TiO x N y LSV polarization curves of IrRu / TiON-5, IrRu / TiON-CS5 and IrRu / TiON-CS6; Figure 11 For IrRu / TiON-1, IrRu NP, commercial IrO2, commercial RuO2 and IrRu / TiO x N y At 10mA cm -2 Chronopotential method test curve under the given conditions; Figure 12 Polarization curves of a proton exchange membrane water electrolyzer using IrRu / TiON-1 and commercial IrO2 as anode catalysts (test conditions: temperature 80℃, atmospheric pressure, 0.1 mol L⁻¹). -1 The flow rate of the HClO4 aqueous solution was 600 mL / min. -1 ); Figure 13 0.5A cm -2 The chronopotential method test curves of a proton exchange membrane water electrolyzer using IrRu / TiON-1 and commercial IrO2 as anode catalysts are shown below. Detailed Implementation

[0034] The present invention will be further described below with reference to embodiments.

[0035] Example 1 The preparation process of the IrRu / TiON acidic oxygen evolution reaction electrocatalyst is as follows: Figure 1 As shown, the specific steps are as follows: (1) Preparation of TiON porous nanoribbons: Weigh 1 g TiO2, 10 g NaOH and 1 g CTAB and add them to 50 mL deionized water. After stirring evenly, transfer it to a hydrothermal reactor and react at 180 °C for 24 hours. After cooling to room temperature, separate the solid and liquid. Wash the precipitate with deionized water until neutral, and then wash it with anhydrous ethanol to completely remove CTAB. After vacuum drying at 60 °C, obtain sodium titanate nanoribbons. Disperse 0.5 g sodium titanate nanoribbons ultrasonically in 50 mL of 0.1 mol / L HCl solution, stir for 2 hours, filter, wash with deionized water until neutral, and then vacuum dry at 60 °C to obtain hydrotitanic acid nanoribbons. Place the hydrotitanic acid nanoribbons in an NH3 atmosphere, first heat to 400 °C at a rate of 5 °C / min and hold for 2 hours, then heat to 700 °C at a rate of 5 °C / min and hold for 2 hours, and then cool to room temperature to obtain TiON porous nanoribbons, labeled as TiON-1.

[0036] (2) Preparation of IrRu / TiON acidic oxygen evolution reaction electrocatalyst: 18.6 mg IrCl3·xH2O (Aladdin, Ir content 56.22%) and 45 mg RuCl3·xH2O (Aladdin, Ru content 36.28%) were stirred and dispersed in 50 mL of ethylene glycol. 40 mg TiON-1 was added and ultrasonically dispersed. The resulting suspension was reacted at 150 °C for 3 hours, naturally cooled to room temperature, centrifuged, and the precipitate was repeatedly washed with anhydrous ethanol. After vacuum drying at 60 °C, IrRu / TiON acidic oxygen evolution reaction electrocatalyst was obtained and labeled as IrRu / TiON-1.

[0037] Example 2 (1) Preparation of TiON porous nanoribbons: Weigh 1 g TiO2, 10 g NaOH and 1 g CTAB and add them to 50 mL deionized water. After stirring evenly, transfer it to a hydrothermal reactor and react at 190 °C for 36 hours. After cooling to room temperature, separate the solid and liquid. Wash the precipitate with deionized water until neutral, and then wash it with anhydrous ethanol to completely remove CTAB. After vacuum drying at 60 °C, obtain sodium titanate nanoribbons. Disperse 0.5 g sodium titanate nanoribbons ultrasonically in 50 mL of 0.3 mol / L HCl solution, stir for 3 hours, filter, wash with deionized water until neutral, and then vacuum dry at 60 °C to obtain hydrotitanic acid nanoribbons. Place the hydrotitanic acid nanoribbons in an NH3 atmosphere, first heat to 400 °C at a rate of 5 °C / min and hold for 2 hours, then heat to 800 °C at a rate of 5 °C / min and hold for 2 hours. After cooling to room temperature, obtain TiON porous nanoribbons, labeled as TiON-2.

[0038] (2) Preparation of IrRu / TiON acidic oxygen evolution reaction electrocatalyst: 9.3 mg IrCl3·xH2O (Aladdin, Ir content 56.22%) and 22.5 mg RuCl3·xH2O (Aladdin, Ru content 36.28%) were stirred and dispersed in 25 mL of ethylene glycol. 20 mg TiON-2 was added and ultrasonically dispersed. The resulting suspension was reacted at 140 °C for 3 hours, naturally cooled to room temperature, centrifuged, and the precipitate was repeatedly washed with anhydrous ethanol. After vacuum drying at 60 °C, IrRu / TiON acidic oxygen evolution reaction electrocatalyst was obtained and labeled as IrRu / TiON-2.

[0039] Example 3 (1) Preparation of TiON porous nanoribbons: Weigh 1 g TiO2, 10 g NaOH and 1 g CTAB and add them to 50 mL deionized water. After stirring evenly, transfer it to a hydrothermal reactor and react at 200 °C for 24 hours. After cooling to room temperature, separate the solid and liquid. Wash the precipitate with deionized water until neutral, and then wash it with anhydrous ethanol to completely remove CTAB. After vacuum drying at 60 °C, obtain sodium titanate nanoribbons. Disperse 0.5 g sodium titanate nanoribbons ultrasonically in 50 mL of 0.5 mol / L HCl solution, stir for 3 hours, filter, wash with deionized water until neutral, and then vacuum dry at 60 °C to obtain hydrotitanic acid nanoribbons. Place the hydrotitanic acid nanoribbons in an NH3 atmosphere, first heat to 400 °C at a rate of 5 °C / min and hold for 2 hours, then heat to 700 °C at a rate of 5 °C / min and hold for 2 hours. After cooling to room temperature, obtain TiON porous nanoribbons, labeled as TiON-3.

[0040] (2) Preparation of IrRu / TiON acidic oxygen evolution reaction electrocatalyst: 18.6 mg IrCl3·xH2O (Aladdin, Ir content 56.22%) and 45 mg RuCl3·xH2O (Aladdin, Ru content 36.28%) were stirred and dispersed in 50 mL ethylene glycol. 40 mg TiON-3 was added and ultrasonically dispersed. The resulting suspension was reacted at 160 °C for 4 hours, naturally cooled to room temperature, centrifuged, and the precipitate was repeatedly washed with anhydrous ethanol. After vacuum drying at 60 °C, IrRu / TiON acidic oxygen evolution reaction electrocatalyst was obtained and labeled as IrRu / TiON-3.

[0041] Example 4 (1) Preparation of TiON porous nanoribbons: Weigh 1 g TiO2, 10 g NaOH and 1 g CTAB and add them to 50 mL deionized water. After stirring evenly, transfer it to a hydrothermal reactor and react at 170 °C for 36 hours. After cooling to room temperature, separate the solid and liquid. Wash the precipitate with deionized water until neutral, and then wash it with anhydrous ethanol to completely remove CTAB. After vacuum drying at 60 °C, obtain sodium titanate nanoribbons. Disperse 0.5 g sodium titanate nanoribbons ultrasonically in 50 mL of 0.2 mol / L HCl solution, stir for 3 hours, filter, wash with deionized water until neutral, and then vacuum dry at 60 °C to obtain hydrotitanic acid nanoribbons. Place the hydrotitanic acid nanoribbons in an NH3 atmosphere, first heat to 400 °C at a rate of 5 °C / min and hold for 2 hours, then heat to 800 °C at a rate of 5 °C / min and hold for 4 hours. After cooling to room temperature, obtain TiON porous nanoribbons, labeled as TiON-4.

[0042] (2) Preparation of IrRu / TiON acidic oxygen evolution reaction electrocatalyst: 18.6 mg IrCl3·xH2O (Aladdin, Ir content 56.22%) and 45 mg RuCl3·xH2O (Aladdin, Ru content 36.28%) were stirred and dispersed in 50 mL ethylene glycol. 40 mg TiON-4 was added and ultrasonically dispersed. The resulting suspension was reacted at 160 °C for 4 hours, naturally cooled to room temperature, centrifuged, and the precipitate was repeatedly washed with anhydrous ethanol. After vacuum drying at 60 °C, IrRu / TiON acidic oxygen evolution reaction electrocatalyst was obtained and labeled as IrRu / TiON-4.

[0043] Example 5 The only difference between Example 5 and Example 1 is that Example 5 uses a single nitriding process, as detailed below: (1) Preparation of TiON porous nanoribbons: Weigh 1 g TiO2, 10 g NaOH and 1 g CTAB and add them to 50 mL deionized water. After stirring evenly, transfer it to a hydrothermal reactor and react at 180 °C for 24 hours. After cooling to room temperature, separate the solid and liquid. Wash the precipitate with deionized water until neutral, and then wash it with anhydrous ethanol to completely remove CTAB. After vacuum drying at 60 °C, obtain sodium titanate nanoribbons. Disperse 0.5 g sodium titanate nanoribbons ultrasonically in 50 mL of 0.1 mol / L HCl solution, stir for 2 hours, filter, wash with deionized water until neutral, and vacuum dry at 60 °C to obtain hydrotitanic acid nanoribbons. Place the hydrotitanic acid nanoribbons in an NH3 atmosphere, heat to 700 °C at a rate of 5 °C / min and hold for 2 hours. Cool to room temperature to obtain TiON porous nanoribbons, labeled as TiON-5.

[0044] (2) Preparation of IrRu / TiON acidic oxygen evolution reaction electrocatalyst: 18.6 mg IrCl3·xH2O (Aladdin, Ir content 56.22%) and 45 mg RuCl3·xH2O (Aladdin, Ru content 36.28%) were stirred and dispersed in 50 mL of ethylene glycol. 40 mg TiON-5 was added and ultrasonically dispersed. The resulting suspension was reacted at 150 °C for 3 hours, naturally cooled to room temperature, centrifuged, and the precipitate was repeatedly washed with anhydrous ethanol. After vacuum drying at 60 °C, IrRu / TiON acidic oxygen evolution reaction electrocatalyst was obtained and labeled as IrRu / TiON-5.

[0045] Comparative Example 1 18.6 mg IrCl3·xH2O (Aladdin, Ir content 56.22%) and 45 mg RuCl3·xH2O (Aladdin, Ru content 36.28%) were stirred and dispersed in 50 mL of ethylene glycol. The mixture was reacted at 150 °C for 3 hours, allowed to cool naturally to room temperature, centrifuged, and the precipitate was repeatedly washed with anhydrous ethanol. After vacuum drying at 60 °C, IrRu nanoparticles were obtained and labeled as IrRu NP.

[0046] Comparative Example 2 This invention selects the IrRu / TiO prepared in Example 1 of the patent application number 202411535010.5. x N y The catalytic performance of the nanoribbon composite catalyst was compared using it as a control sample.

[0047] Comparative Example 3 Commercial IrO2, purchased from Energetic Chemicals.

[0048] Comparative Example 4 Commercial RuO2, purchased from Energie Chemicals.

[0049] Comparative Example 5 The only difference between Comparative Example 5 and Example 1 is that the nitriding temperature is 600°C.

[0050] (1) Preparation of TiON porous nanoribbons: Weigh 1 g TiO2, 10 g NaOH and 1 g CTAB and add them to 50 mL deionized water. After stirring evenly, transfer it to a hydrothermal reactor and react at 180 °C for 24 hours. After cooling to room temperature, separate the solid and liquid. Wash the precipitate with deionized water until neutral, and then wash it with anhydrous ethanol to completely remove CTAB. After vacuum drying at 60 °C, obtain sodium titanate nanoribbons. Disperse 0.5 g sodium titanate nanoribbons ultrasonically in 50 mL of 0.1 mol / L HCl solution, stir for 2 hours, filter, wash with deionized water until neutral, and then vacuum dry at 60 °C to obtain hydrotitanic acid nanoribbons. Place the hydrotitanic acid nanoribbons in an NH3 atmosphere, first heat to 400 °C at a rate of 5 °C / min and hold for 2 hours, then heat to 600 °C at a rate of 5 °C / min and hold for 2 hours, and then cool to room temperature to obtain TiON porous nanoribbons, labeled as TiON-CS5.

[0051] (2) Preparation of IrRu / TiON acidic oxygen evolution reaction electrocatalyst: 18.6 mg IrCl3·xH2O (Aladdin, Ir content 56.22%) and 45 mg RuCl3·xH2O (Aladdin, Ru content 36.28%) were stirred and dispersed in 50 mL of ethylene glycol. 40 mg TiON-CS5 was added and ultrasonically dispersed. The resulting suspension was reacted at 150 °C for 3 hours, naturally cooled to room temperature, centrifuged, and the precipitate was repeatedly washed with anhydrous ethanol. After vacuum drying at 60 °C, IrRu / TiON acidic oxygen evolution reaction electrocatalyst was obtained and labeled as IrRu / TiON-CS5.

[0052] Comparative Example 6 The only difference between Comparative Example 6 and Example 1 is that the nitriding temperature is 850°C.

[0053] (1) Preparation of TiON porous nanoribbons: Weigh 1 g TiO2, 10 g NaOH and 1 g CTAB and add them to 50 mL deionized water. After stirring evenly, transfer it to a hydrothermal reactor and react at 180 °C for 24 hours. After cooling to room temperature, separate the solid and liquid. Wash the precipitate with deionized water until neutral, and then wash it with anhydrous ethanol to completely remove CTAB. After vacuum drying at 60 °C, obtain sodium titanate nanoribbons. Disperse 0.5 g sodium titanate nanoribbons ultrasonically in 50 mL of 0.1 mol / L HCl solution, stir for 2 hours, filter, wash with deionized water until neutral, and then vacuum dry at 60 °C to obtain hydrotitanic acid nanoribbons. Place the hydrotitanic acid nanoribbons in an NH3 atmosphere, first heat to 400 °C at a rate of 5 °C / min and hold for 2 hours, then heat to 850 °C at a rate of 5 °C / min and hold for 2 hours, and then cool to room temperature to obtain TiON porous nanoribbons, labeled as TiON-CS6.

[0054] (2) Preparation of IrRu / TiON acidic oxygen evolution reaction electrocatalyst: 18.6 mg IrCl3·xH2O (Aladdin, Ir content 56.22%) and 45 mg RuCl3·xH2O (Aladdin, Ru content 36.28%) were stirred and dispersed in 50 mL of ethylene glycol. 40 mg TiON-CS6 was added and ultrasonically dispersed. The resulting suspension was reacted at 150 °C for 3 hours, naturally cooled to room temperature, centrifuged, and the precipitate was repeatedly washed with anhydrous ethanol. After vacuum drying at 60 °C, IrRu / TiON acidic oxygen evolution reaction electrocatalyst was obtained and labeled as IrRu / TiON-CS6.

[0055] Performance testing Figure 2 XRD patterns of TiON-1, IrRu NP, and IrRu / TiON-1 are shown. As shown by the green dashed line in the figure, after loading IrRu nanoparticles, the intensity of the diffraction characteristic peaks of IrRu / TiON-1 decreases and shifts to the left compared with TiON-1, indicating that there is an interaction between the IrRu nanoparticles and the TiON porous nanoribbon support. As shown by the blue dashed line, diffraction characteristic peaks of IrRu nanoalloy particles appear in IrRu / TiON-1, with 38.6°, 41.8°, 43.8°, 57.9°, 69.5°, 78.4°, and 84.8° corresponding to the (100), (002), (101), (102), (110), (103), and (112) crystal planes of IrRu nanoalloy particles, respectively.

[0056] Figure 3 SEM images of IrRu / TiON-1 (a) in Example 1 and IrRu / TiON-CS6 (b) in Comparative Example 6. Figure 3The results show that IrRu / TiON-1 has a typical porous nanoribbon morphology, while IrRu / TiON-CS6 exhibits a distinctly fragmented morphology. This is because Comparative Example 6 used an excessively high nitriding temperature (850℃).

[0057] Figure 4 TEM image (a) and HRTEM image (b) of IrRu / TiON-1. Figure 4 The results show that IrRu nanoparticles are uniformly dispersed on the TiON-1 support with a narrow size distribution and an average particle size of 2.05 nm.

[0058] Figure 5 Nitrogen adsorption-desorption isotherms (a) and Barrett-Joyner-Halenda (BJH) pore size distribution curves (b) for IrRu / TiON-1. Figure 5 The nitrogen adsorption-desorption isotherms and pore size distribution curves show that the BET specific surface area of ​​IrRu / TiON-1 is 53.9 m². 2 / g, and has a hierarchical porous structure.

[0059] Figure 6 AC-HAADF-STEM image (a) and corresponding elemental distribution map (b) of IrRu / TiON-1. Figure 6 It visually demonstrates the uniform distribution of elements such as Ir, Ru, N, O, and Ti.

[0060] Figure 7 AC-HAADF-STEM images of IrRu nanoparticles and their corresponding FFT patterns and crystal structure models are shown in (a), along with the line-scan EELS spectrum of the interface between the TiON-1 support and the IrRu nanoparticles (b). The Fast Fourier Transform (FFT) pattern in (a) further confirms the atomic arrangement in the hexagonal close-packed (hcp) structure of the IrRu nanoparticles; the line-scan electron energy loss spectrum (EELS) along the interface in (b) shows that Ru, N, and Ti signals are present simultaneously in the interface layer between IrRu and TiON-1, confirming the strong interfacial electronic interaction between IrRu and TiON-1.

[0061] Figure 8 AFM image (a) and surface potential diagram (b) of IrRu / TiON-1. Figure 8 The results show that there is a surface potential difference of 64 mV between IrRu and TiON-1, which is due to the transfer of electrons from TiON-1 to IrRu nanoparticles at the interface.

[0062] Figure 9This diagram illustrates the "electron supply pool effect" in IrRu / TiON-1. The TiON-1 carrier, with its strong electron supply capacity, induces electron transfer from TiON-1 and Ir sites to Ru sites, triggering the "electron supply pool effect." On the one hand, this provides sufficient electron compensation for Ru sites, continuously stabilizing their low valence state; on the other hand, it promotes the formation of highly active, high-valence Ir species.

[0063] Figure 10 For IrRu / TiON-1, IrRu NP, commercial IrO2, commercial RuO2, IrRu / TiO x N y LSV polarization curves of IrRu / TiON-5, IrRu / TiON-CS5 and IrRu / TiON-CS6. Figure 10 The results show that IrRu / TiON-1 in Example 1 achieves 10 mA cm⁻¹. -2 The overpotential required for the current density is only 224 mV, which is significantly better than that of IrRu NP (294 mV) in Comparative Example 1, commercial IrO2 (448 mV) in Comparative Example 3, commercial RuO2 (373 mV) in Comparative Example 4, and IrRu / TiO in Comparative Example 2. x N y The overpotential of IrRu / TiON-1 (250 mV) can be attributed to the "electron supply pool effect" induced by the introduction of TiON-1, which significantly enhances the acidic oxygen evolution reaction (OER) activity of the IrRu / TiON-1 catalyst. Furthermore, the overpotential of IrRu / TiON-1 is superior to that of IrRu / TiON-5 (238 mV) in Example 5, IrRu / TiON-CS5 (243 mV) in Comparative Example 5, and IrRu / TiON-6 (252 mV) in Comparative Example 6, indicating that the nitriding temperature and multi-stage nitriding process have a significant impact on the acidic OER activity of the catalyst.

[0064] Figure 11 For IrRu / TiON-1, IrRuNP, commercial IrO2, commercial RuO2 and IrRu / TiO x N y At 10mA cm -2 Chronopotential method test curve under certain conditions. Figure 11 The results show that IrRu / TiON-1 exhibits less voltage decay over 330 hours compared to IrRu / TiO in the comparative patent. x N y In the 200-hour voltage decay test, it showed excellent stability of the oxygen evolution reaction, while IrRu NP, commercial IrO2, and commercial RuO2 showed significant voltage decay after 90 hours, 40 hours, and 2 hours, respectively.

[0065] Figure 12Polarization curves of a proton exchange membrane water electrolyzer using IrRu / TiON-1 and commercial IrO2 as anode catalysts (test conditions: temperature 80℃, atmospheric pressure, 0.1 mol / L). -1 The flow rate of the HClO4 aqueous solution was 600 mL / min. -1 ). Figure 12 The results show that the IrRu / TiON-1-based proton exchange membrane water electrolyzer exhibits superior water electrolysis performance, requiring only 1.677, 1.839, and 1.953 V to achieve 1.0, 2.0, and 3.0 A cm⁻¹ electrolysis, respectively. -2 Its operating current density is superior to that of commercial IrO2, which is 1.818, 2.056, and 2.242 V.

[0066] Figure 13 0.5A cm -2 Below are the chronopotential test curves of a proton exchange membrane water electrolyzer using IrRu / TiON-1 and commercial IrO2 as anode catalysts (loading: IrRu / TiON-1 is 0.8 mg). Ir+Ru cm -2 IrO2 was 2.0 mg. Ir cm -2 ). Figure 13 The results show that the IrRu / TiON-1-based proton exchange membrane water electrolyzer operates at 0.5 A cm⁻¹. -2 It exhibits excellent stability under current density conditions, with a voltage decay rate of only 0.087 mV h after 450 hours of continuous operation. -1 In contrast, the voltage decay rate of a proton exchange membrane water electrolyzer based on commercial IrO2 after 200 hours of continuous operation is 0.45 mV / h. -1 .

Claims

1. A method for preparing an IrRu / TiON acidic oxygen evolution reaction electrocatalyst, characterized in that: Includes the following steps: 1) Preparation of TiON porous nanoribbons: Sodium titanate nanoribbons were prepared by hydrothermal reaction of TiO2, NaOH and surfactant in water; the sodium titanate nanoribbons were dispersed in an acid solution for ion exchange reaction to obtain hydrogen titanate nanoribbons; the hydrogen titanate nanoribbons were placed in an NH3 atmosphere for multi-stage nitriding and cooling to obtain TiON porous nanoribbons. The multi-stage nitriding process includes: first, heating to 400-450°C at a rate of 3-7°C / min and holding for 1-3 hours; then heating to 700-800°C at a rate of 3-7°C / min and holding for 2-4 hours. 2) Preparation of IrRu / TiON acidic oxygen evolution reaction electrocatalyst: Ir precursor and Ru precursor are dispersed in polyol, and TiON porous nanobelts are added and dispersed evenly to obtain a suspension. After reduction reaction at 140~160℃, IrRu nanoparticles with an average particle size of 2.05nm are formed on the TiON porous nanobelts, resulting in an IrRu / TiON acidic oxygen evolution reaction electrocatalyst with a total loading of 30~50wt% of Ir and Ru elements. An "electron supply pool effect" is formed between the TiON porous nanobelt support and the IrRu nanoparticles.

2. The preparation method according to claim 1, characterized in that: In step 1), the hydrothermal reaction specifically includes: adding TiO2, NaOH and surfactant into water, stirring evenly, and then hydrothermally reacting at 160~200℃ for 12~36 hours. After cooling, the solid and liquid are separated, the precipitate is taken, washed, and dried to obtain sodium titanate nanoribbons.

3. The preparation method according to claim 1 or 2, characterized in that: In step 1): The mass ratio of TiO2, NaOH, and surfactant is 1:(5~10):(0.5~1). The surfactant is hexadecyltrimethylammonium bromide.

4. The preparation method according to claim 2, characterized in that: In step 1): the washing includes: first washing the precipitate with water until neutral, and then washing with anhydrous ethanol to completely remove the surfactant.

5. The preparation method according to claim 1, characterized in that: In step 1): the acid solution is a 0.1~0.5 mol / L HCl solution.

6. The preparation method according to claim 1 or 5, characterized in that: In step 1), the ion exchange reaction takes 2 to 4 hours.

7. The preparation method according to claim 1 or 5, characterized in that: In step 1): After the ion exchange reaction, the reaction product is filtered, washed with water until neutral, and dried to obtain hydrogen titanate nanoribbons.

8. The preparation method according to claim 1, characterized in that: In step 2), the molar ratio of Ir element in the Ir precursor to Ru element in the Ru precursor is (1:3) to (3:1).

9. The preparation method according to claim 1 or 8, characterized in that: In step 2): The reduction reaction takes 2 to 4 hours; After the reduction reaction, the reaction product was cooled to room temperature, centrifuged, and the precipitate was repeatedly washed with anhydrous ethanol and dried to obtain the IrRu / TiON acidic oxygen evolution reaction electrocatalyst.

10. The application of the IrRu / TiON acidic oxygen evolution reaction electrocatalyst obtained by the preparation method according to any one of claims 1-9 in proton exchange membrane water electrolysis, characterized in that: The IrRu / TiON acidic oxygen evolution reaction electrocatalyst is used as the anode electrocatalyst.

Citation Information

Patent Citations

  • IrRu / TiOxNy nanobelt composite catalyst and preparation method thereof

    CN119386915A